‘We no longer live in a time of separation’: A comparative analysis of how editorial and commercial integration became a norm - Cornia, A; Sehl, A; Nielsen, R (SAGE Publications, 2018)
The separation between editorial and business activities of news organisations has long been a fundamental norm of journalism. Journalists have traditionally considered this separation as both an ethical principle and an organisational solution to preserve their professional autonomy and isolate their newsrooms from profit-driven pressures exerted by advertising, sales and marketing departments. However, many news organisations are increasingly integrating their editorial and commercial operations. Based on 41 interviews conducted at 12 newspapers and commercial broadcasters in six European countries, we analyse how editors and business managers describe the changing relationship between their departments. Drawing on previous research on journalistic norms and change, we focus on how interviewees use rhetorical discourses and normative statements to de-construct traditional norms, build new professionally accepted norms and legitimise new working practices. We find, first, that the traditional norm of separation no longer plays the central role that it used to. Both editors and managers are working to foster a cultural change that is seen as a prerequisite for organisational adaptation to an increasingly challenging environment. Second, we find that a new norm of integration, based on the values of collaboration, adaptation and business thinking, has emerged. Third, we show how the interplay between declining and emerging norms involves a difficult negotiation. Whereas those committed to the traditional norm see commercial considerations as a threat to professional autonomy, our interviewees see the emerging norm as a new way of ensuring professional autonomy by working with other parts of the organisation to jointly ensure commercial sustainability.